A sealant silicone gel material for humanoid robot joint connections and a method for preparing the same

CN122917547APending Publication Date: 2026-10-16ZHEJIANG LINGZHIYUAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611326199.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对现有密封材料在人形机器人关节连接处应用中存在的压缩永久变形、防尘和循环耐久性能难以兼顾的问题,本发明提供一种人形机器人关节连接处密封硅凝胶材料及其制备方法

Benefits of technology

1.图1所示实施例1片层复合弹性微粒表面可见彼此间隔的片状结构,未形成连续致密包覆层。在本申请列明的模拟工装及测试条件下,实施例1-5均获得IP6X防尘判定结果,而对比例1-8获得IP5X判定结果;所述判定仅对应本申请模拟工装,不等同于机器人整机防护等级。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917547A_ABST
    Figure CN122917547A_ABST
Patent Text Reader

Abstract

The application discloses a kind of humanoid robot joint connecting place sealing silicon gel material and preparation method thereof. According to mass parts, including vinyl terminated polydimethylsiloxane 100 parts, hydrogen-containing silicone oil 4.0-10.0 parts, vinyl MQ silicone resin dispersion 4.0-12.0 parts, lamellar composite elastic microparticle component 8.0-20.0 parts, hydrophobic fumed silica 1.0-5.0 parts, bonding accelerator 0.5-2.0 parts, platinum-vinylsiloxane complex catalyst working fluid 0.10-0.50 parts and alkyne alcohol inhibitor 0.01-0.06 parts.The lamellar composite elastic microparticle includes crosslinked silicone rubber elastic microparticle and silane-treated synthetic mica sheet distributed on its surface, and does not form continuous dense coating layer.Under the test conditions listed in the application, the material has lower compression permanent deformation and water absorption rate, and obtains IP6X dustproof determination result in simulated joint tooling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sealing materials technology, specifically to a silicone gel material for sealing joints of humanoid robots and its preparation method. Background Technology

[0002] During humanoid robots' walking, running, and carrying movements, their joints frequently undergo multi-degree-of-freedom rotation and bending motions. Assembly gaps exist between the joint drive components (such as motors, reducers, and encoders) and the joint housing, and circumferential gaps also exist at the joint cable exit points. If dust, moisture, and impurities enter the joint through these gaps, it will lead to accelerated wear of the drive components, sensor signal drift, and cable insulation aging, and in severe cases, joint jamming or failure. Therefore, a sealing structure is necessary at the joint connections.

[0003] In existing technologies, commonly used sealing materials for humanoid robot joint connections include thermoplastic elastomer seals, polyurethane casting adhesives, and ordinary silicone rubber. Thermoplastic elastomer seals are prone to stress relaxation and permanent deformation under long-term compression conditions, making it difficult to maintain stable sealing pressure after prolonged service. Polyurethane casting adhesives have insufficient hydrolytic resistance, their mechanical properties deteriorate significantly after absorbing water, and their high hardness results in poor responsiveness to joint movement. While ordinary silicone rubber possesses good weather resistance and flexibility, it suffers from large permanent compression deformation and short fatigue life under high-frequency cyclic motion conditions in humanoid robot joints, leading to cracking and sealing failure after only a few thousand cycles. Furthermore, ordinary silicone rubber seals have insufficient barrier properties against fine dust particles, failing to meet IP6X dustproof rating requirements, and their adhesion strength to metal shells and engineering plastic substrates is relatively low, making them prone to interfacial peeling and sealing failure during joint movement.

[0004] To improve the overall performance of sealing materials, existing technologies typically reinforce silicone rubber by adding inorganic fillers such as silica and calcium carbonate. However, conventional powder fillers exhibit poor dispersion uniformity in the silicone rubber matrix, are prone to agglomeration, and have weak interfacial bonding with the matrix. During cyclic deformation, they are susceptible to interfacial delamination, which accelerates material fatigue failure. Some technologies have attempted to use mica sheets as barrier fillers, but untreated mica has poor compatibility with the silicone rubber matrix, making it difficult to achieve uniform dispersion and stable bonding.

[0005] Therefore, there is an urgent need for a sealing silicone gel material that combines low compression set, high dustproof performance, and long cyclic fatigue life to meet the sealing requirements of humanoid robot joints. Summary of the Invention

[0006] To address the challenge of simultaneously achieving compression set, dustproofing, and cyclic durability in existing sealing materials used in humanoid robot joint connections, this invention provides a silicone gel material for sealing humanoid robot joint connections and its preparation method. This material incorporates a layered composite elastic microparticle component, distributing silane-treated synthetic mica sheets in a discontinuous layered manner on the surface and outer layer of the silicone rubber elastic microparticles, thereby improving the dispersion and interfacial stability of the mica sheets within the silicone gel matrix.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a sealing silicone gel material for the joint connection of a humanoid robot, comprising the following components by weight: 100 parts of vinyl-terminated polydimethylsiloxane, 4.0-10.0 parts of hydrogen-containing silicone oil, 4.0-12.0 parts of vinyl MQ silicone resin dispersion, 8.0-20.0 parts of sheet composite elastic microparticle component, 1.0-5.0 parts of hydrophobic fumed silica, 0.5-2.0 parts of adhesion promoter, 0.10-0.50 parts of platinum-vinylsiloxane complex catalyst working solution, and 0.01-0.06 parts of alkynyl alcohol inhibitor.

[0008] In some embodiments, the dispersion medium of the vinyl MQ silicone resin dispersion is vinyl-terminated polydimethylsiloxane; 100 parts of vinyl-terminated polydimethylsiloxane do not include the mass of the dispersion medium; the platinum content of the platinum-vinylsiloxane complex catalyst working solution is 2000-5000 mg / kg; the raw materials for preparing the sheet-like composite elastic microparticle component, by mass, include: 100 parts vinyl-terminated polydimethylsiloxane, 3.0-8.0 parts hydrogen-containing silicone oil, 6.0-16.0 parts hydrophobic fumed silica, 12.0-30.0 parts synthetic mica, 1.5-4.0 parts vinyltriethoxysilane, 0.05-0.25 parts platinum-vinylsiloxane complex catalyst working solution, and 0.01-0.06 parts alkynyl alcohol inhibitor.

[0009] In some embodiments, the sheet composite elastic microparticle component further comprises silicone rubber elastic microparticles formed by crosslinking the vinyl-terminated polydimethylsiloxane and the hydrogen-containing silicone oil, and silane-treated synthetic mica sheets distributed at intervals on the surface of the silicone rubber elastic microparticles; the silane-treated synthetic mica sheets do not form a continuous dense coating layer.

[0010] In some embodiments, the vinyl-terminated polydimethylsiloxane is further composed of a first vinyl-terminated polydimethylsiloxane and a second vinyl-terminated polydimethylsiloxane; the first vinyl-terminated polydimethylsiloxane typically has a kinematic viscosity of 100 mmHg at 25°C. 2 / s, vinyl mass fraction is 0.80%-1.20%; the typical kinematic viscosity of the second vinyl-terminated polydimethylsiloxane at 25°C is 5000 mm⁻¹. 2 / s, the vinyl mass fraction is 0.10%-0.13%; the mass ratio of the first vinyl-terminated polydimethylsiloxane to the second vinyl-terminated polydimethylsiloxane is 35:65-60:40.

[0011] In some embodiments, the kinematic viscosity of the hydrogen-containing silicone oil at 25°C is further 25-35 mm. 2 / s, the molar fraction of methyl hydrogen siloxane structural units is 25%-35%.

[0012] In some embodiments, the vinyl MQ silicone resin dispersion further comprises 20%-25% vinyl MQ silicone resin by mass, and has a kinematic viscosity of 4500-7000 mmHg at 25°C. 2 / s, with a vinyl equivalent of 0.20-0.30 eq / kg.

[0013] In some embodiments, the median volumetric particle size of the layered composite elastic microparticle component is 80-250 μm; the median volumetric particle size of the synthetic mica is 5-20 μm, and the layer thickness is 0.2-1.5 μm; the BET specific surface area of ​​the hydrophobic fumed silica is selected from 90-130 m². 2 / g, 150-190m 2 / g or 225-275m 2 / g.

[0014] In some embodiments, the adhesion promoter is further composed of γ-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane in a mass ratio of 1:0.30 to 1:1.00; the alkynol inhibitor is one or both of 1-ethynylcyclohexanol and 2-methyl-3-butyn-2-ol.

[0015] In some embodiments, the method for preparing the sheet-like composite elastic microparticle component further includes the following steps: A1. The synthetic mica was dried at 105-120℃ for 2-4 hours. Then, the synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:8 to 1:15, where the mass ratio of ethanol to water in the ethanol-water mixture was 90:10 to 96:4. Vinyltriethoxysilane was added, and the pH of the system was adjusted to 4.2-4.8 with acetic acid. The mixture was stirred at 50-60℃ and 400-800 r / min for 60-120 min, filtered, washed 2-3 times with the ethanol-water mixture, and dried at 70-85℃ for 4-8 hours to obtain silane-treated synthetic mica.

[0016] A2. At 20-30℃, vinyl-terminated polydimethylsiloxane and hydrophobic fumed silica are stirred at 600-1000 r / min for 15-30 min, alkynyl alcohol inhibitors and hydrogen-containing silicone oil are added, and the mixture is stirred at 300-600 r / min for 5-10 min. Then, platinum-vinylsiloxane complex catalyst is added, and the mixture is stirred at 200-400 r / min for 2-5 min to obtain a silicone rubber reaction mixture.

[0017] A3. The silicone rubber reaction mixture is added to a polyvinyl alcohol aqueous solution with a mass fraction of 0.8%-1.5%, wherein the degree of alcoholysis of the polyvinyl alcohol is 87.0%-89.0%; the mass ratio of the silicone rubber reaction mixture to the polyvinyl alcohol aqueous solution is 1:4-1:8, and dispersed at 900-1500 r / min for 8-15 min to form silicone rubber droplets; the rotation speed is adjusted to 400-700 r / min, and the silane-treated mica is added within 5-10 min, and stirring is continued for 10-20 min, followed by holding at 65-80℃ for 60-180 min to obtain crosslinked silicone rubber droplets.

[0018] A4. Filter the cross-linked silicone rubber droplets, wash them 2-3 times with deionized water, dry them at 60-75℃ for 6-10 hours, and sieve them to obtain a layered composite elastic microparticle component with a median particle size of 80-250 μm.

[0019] This invention also provides a method for preparing a sealing silicone gel material for the joint connections of a humanoid robot, comprising the following steps: S1. Add vinyl-terminated polydimethylsiloxane, vinyl MQ silicone resin dispersion and hydrophobic fumed silica to a stirring device and stir for 15-30 min at 20-35℃ and 600-1000 r / min; add the sheet composite elastic microparticle component and adhesion promoter, stir for 15-30 min at 20-35℃ and 400-800 r / min, and then degas for 10-20 min under a vacuum of -0.095 to -0.080 MPa to obtain the basic mixture.

[0020] S2. Add alkynyl alcohol inhibitor and hydrogen-containing silicone oil to the basic mixture, and stir for 5-10 min at 20-30℃ and 200-500 r / min; then add platinum-vinylsiloxane complex catalyst, and stir for 3-6 min at 20-30℃ and 200-400 r / min to obtain a silicone gel mixture.

[0021] S3. Degas the silicone gel mixture under a vacuum of -0.098 to -0.085 MPa for 5-15 minutes, then inject it into the area to be sealed at the joint connection of the humanoid robot, and cure it at 60-80°C for 45-120 minutes.

[0022] In some embodiments, further, in step S1, the hydrophobic fumed silica is dried at 110-130°C for 2-4 hours before being added to the stirring equipment; the sheet-like composite elastic microparticle component is dried at 65-80°C for 2-4 hours before being added to the stirring equipment; the material temperature in both steps S1 and S2 is controlled below 35°C.

[0023] In some embodiments, further, in step S3, the area to be sealed is the connection gap between adjacent joint housings, the annular gap between the joint drive assembly and the joint housing, or the circumferential gap at the joint cable lead-out position; the thickness of the filling layer formed by the silicone gel mixture before curing is 0.5-5.0 mm.

[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. Figure 1 The surface of the sheet-like composite elastic microparticles in Example 1 shows a sheet-like structure spaced apart from each other, without forming a continuous dense coating layer. Under the simulated tooling and testing conditions specified in this application, Examples 1-5 all obtained IP6X dustproof ratings, while Comparative Examples 1-8 obtained IP5X ratings; these ratings only correspond to the simulated tooling of this application and are not equivalent to the overall protection level of the robot.

[0025] 2. Synthetic mica treated with vinyltriethoxysilane retains the mica skeleton absorption in FTIR and exhibits or enhances organic group-related absorption. Compared with a comparative example using untreated synthetic mica, the relevant examples show different tensile strength, compression set, water absorption, and cyclic fatigue results under the test conditions of this application; these results are used to illustrate the relevance under specific formulations and processes and do not limit the formation of a particular type of covalent bond.

[0026] 3. Figure 1The surface SEM was used to confirm that the silane-treated synthetic mica flakes were spaced apart on the particle surface and did not form a continuous dense coating layer; the surface image was not used to determine the three-dimensional distribution or the depth of the flake embedding within the particles.

[0027] 4. Visible gaps exist between adjacent silane-treated synthetic mica sheets, so that the surface of the silicone rubber elastic microparticles still retains a continuous silicone rubber matrix region; the elongation at break, compression set and cyclic fatigue properties of the material shall be based on the test results listed in this application.

[0028] 5. The adhesion promoter is composed of γ-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Under the simulated tooling and substrate conditions of this application, the examples containing the adhesion promoter have different dustproof and cyclic fatigue results compared with the comparative examples without the adhesion promoter; the specific results vary with the substrate, surface treatment, and tooling structure.

[0029] 6. The vinyl-terminated polydimethylsiloxane is composed of a first vinyl-terminated polydimethylsiloxane and a second vinyl-terminated polydimethylsiloxane with different kinematic viscosities, in a mass ratio of 35:65-60:40, and is used to adjust the mechanical properties after mixing, filling and curing within the range of commercial raw materials and formulations listed in this application. Attached Figure Description

[0030] Figure 1 This is a SEM image of the sheet-like composite elastic microparticle component prepared in Example 1 of the present invention.

[0031] Figure 2 The above are FTIR comparison spectra of the synthetic fluorophlogopite, silane-treated synthetic mica, uncured silicone rubber reaction mixture, and sheet-like composite elastic microparticle components used in Example 1 of this invention. Detailed Implementation

[0032] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Sources and specifications of some raw materials: Unless otherwise stated, the examples and comparative examples use the following commercial raw materials. All parts by weight are based on the actual mass of the commercial raw materials fed into the sample; the parts by weight of the vinyl MQ silicone resin dispersion are based on the mass of the commercial dispersion, wherein the vinyl MQ silicone resin mass fraction is 20%-25%, and the remainder is a vinyl-terminated polydimethylsiloxane dispersion medium. The 100 parts of vinyl-terminated polydimethylsiloxane separately listed in each example do not include this dispersion medium; the parts by weight of the platinum-vinylsiloxane complex catalyst are based on the mass of the diluted working solution.

[0034] The addition-curing raw materials used in Examples 1-5 all adopt the specific commercial specifications described below. When using raw materials from other sources, the first vinyl-terminated polydimethylsiloxane, the second vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, vinyl MQ silicone resin dispersion, and platinum-vinylsiloxane complex catalyst working solution should respectively meet the requirements for kinematic viscosity, vinyl content or equivalent, hydrogen-containing structural unit content, and platinum content listed in this specification, and should not be directly substituted with raw materials that only have the same generic name but different key parameters.

[0035] First-grade vinyl-terminated polydimethylsiloxane; Manufacturer / Model: Gelest, USA, DMS-V21; Specifications: Typical kinematic viscosity at 25°C 100 mmHg 2 / s, vinyl mass fraction 0.80%-1.20%.

[0036] Second vinyl-terminated polydimethylsiloxane; Manufacturer / Model: Gelest, USA DMS-V35; Specifications: Typical kinematic viscosity at 25°C 5000 mmHg 2 / s, vinyl mass fraction 0.10%-0.13%.

[0037] Hydrogen-containing silicone oil; Manufacturer and model: Gelest, USA HMS-301; Specifications: Trimethylsiloxane-terminated methyl hydrogen-containing siloxane-dimethylsiloxane copolymer, kinematic viscosity at 25°C 25-35 mmHg 2 / s, methyl hydrogen siloxane structural unit molar fraction 25%-35%.

[0038] Vinyl MQ silicone resin dispersion; Manufacturer / Model: Gelest Corporation, USA, VQM-135; Specifications: Dispersion of vinyl MQ silicone resin in vinyl-terminated polydimethylsiloxane, resin mass fraction 20%-25%, kinematic viscosity at 25℃ 4500-7000 mmHg 2 / s, vinyl equivalent 0.20-0.30eq / kg.

[0039] Low specific surface area hydrophobic fumed silica; Manufacturer and model: Evonik GmbH, Germany, AEROSIL® R 972; Specifications: BET specific surface area 90-130 m² / g. 2 / g.

[0040] Medium specific surface area hydrophobic fumed silica; Manufacturer and model: Evonik GmbH, Germany, AEROSIL® R 974; Specifications: BET specific surface area 150-190 m² 2 / g.

[0041] High specific surface area hydrophobic fumed silica; Manufacturer / Model: AEROSIL, Evonik GmbH, Germany ® R 976; Parameter: BET specific surface area 225-275m² 2 / g.

[0042] Synthetic mica; Manufacturer: Liaoning Zhongke Crystal Industry Co., Ltd.; Parameters: According to the examples, graded products with a median volumetric particle size D50 of 5±1μm, 12±2μm or 20±2μm were used respectively, and the sheet thickness was in the range of 0.2-1.5μm.

[0043] Natural mica; Manufacturer and model: Imerys Mica MU micronized mica; Parameters: Median particle size D50 is 12±2μm, and the thickness of the lamellae is in the range of 0.2-1.5μm.

[0044] Platinum-vinylsiloxane complex catalyst; Manufacturer and model: Gelest Company, USA, SIP6830.3; Parameters: Karstedt type catalyst mother liquor, platinum mass fraction 3.0%, diluted with DMS-V21 to a working solution with a platinum content of 2000 mg / kg, 3500 mg / kg or 5000 mg / kg before use. The amount added in the examples is based on the mass of the working solution.

[0045] Example 1 (I) Preparation of layered composite elastic microparticle components: Raw material formulation for the preparation of layered composite elastic microparticle components (by mass parts): 100 parts of vinyl-terminated polydimethylsiloxane (47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane); 5.5 parts of hydrogen-containing silicone oil; 11.0 parts of medium specific surface area hydrophobic fumed silica; 21.0 parts of synthetic mica (using synthetic fluorophlogopite powder, with a median particle size D50 of 12±2 μm and a sheet thickness in the range of 0.2-1.5 μm); 2.75 parts of vinyltriethoxysilane; 0.15 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 3500 mg / kg); 0.035 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0046] A1. 21.0 parts of synthetic mica were dried in a forced-air drying oven at 112℃ for 3 hours. The dried synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:11.5 (ethanol:water mass ratio 93:7). 2.75 parts of vinyltriethoxysilane were added, and the pH of the system was adjusted to 4.5 using acetic acid. The mixture was stirred at 55℃ and 600 rpm for 90 minutes. After the reaction was complete, the mixture was filtered, washed twice with an ethanol-water mixture at a mass ratio of 93:7, and the filter cake was dried at 78℃ for 6 hours to obtain silane-treated synthetic mica.

[0047] A2. At 25°C, 47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane, along with 11.0 parts of hydrophobic fumed silica, were added to a reactor and stirred at 800 rpm for 20 min. Then, 0.035 parts of 1-ethynylcyclohexanol and 5.5 parts of hydrogen-containing silicone oil were added, and the mixture was stirred at 450 rpm for 8 min. Finally, 0.15 parts of a platinum-vinylsiloxane complex catalyst working solution with a platinum content of 3500 mg / kg were added, and the mixture was stirred at 300 rpm for 4 min to obtain a silicone rubber reaction mixture.

[0048] A3. The silicone rubber reaction mixture was added to a 1.15% (w / w) polyvinyl alcohol aqueous solution, with a mass ratio of 1:6. The mixture was dispersed at 1200 r / min for 12 min to form silicone rubber droplets. The rotation speed was adjusted to 550 r / min, and the silane obtained in A1 was added over 8 min to treat the synthesized mica. Stirring continued for 15 min. The temperature was then raised to 72℃ and maintained for 120 min to crosslink the silicone rubber droplets, yielding crosslinked silicone rubber droplets.

[0049] A4. The cross-linked silicone rubber droplets were filtered, washed three times with deionized water, dried at 68°C for 8 hours, graded using a standard sieve, and the median volumetric particle size was determined to be 165 μm by laser diffraction, thus obtaining the sheet-like composite elastic microparticle component.

[0050] Figure 1 The image shows a SEM image of the sheet-like composite elastic microparticles prepared in Example 1. As can be seen from the image, the surface of the silicone rubber elastic microparticles exhibits a continuous matrix morphology, on which multiple sheet-like structures of varying sizes and irregular outlines can be observed. Some sheets are attached to the surface of the microparticles, while the edges of some sheets are in contact with the surface of the microparticles, which can be attributed to silane-treated synthetic mica sheets. Visible gaps exist between the sheets, and a continuous, dense coating layer has not been formed. Figure 1 Used to illustrate the surface morphology of the particles in Example 1, but not to determine the three-dimensional distribution or lamellar embedding depth within the particles.

[0051] Figure 2The images show the FTIR contrast spectra of the synthetic fluorophlogopite, silane-treated synthetic mica, uncured silicone rubber reaction mixture, and sheet-like composite elastic microparticles used in Example 1. Curve (a) is located at approximately 1100-1000 cm⁻¹. -1 and 800-400cm -1 The obvious absorption within the range can be attributed to the Si-O stretching vibration and lattice vibration in the silicon-oxygen tetrahedral framework of the synthesized fluorinated phlogopite; curve (b) retains the above-mentioned mica framework absorption, and at approximately 2960 cm⁻¹ -1 and 2900cm -1 The presence or enhancement of aliphatic CH stretching vibration absorptions in the vicinity is consistent with the spectral characteristics of mica treated with silanes containing organic groups. This is observed in curve (c) at approximately 2960-2900 cm⁻¹. -1 Approximately 1260cm -1 Approximately 1090-1020cm -1 and approximately 800cm -1 The absorption at this point is related to the -CH3, Si-CH3, Si-O-Si, and Si-C structures in the silicone rubber system, respectively, and is concentrated at approximately 2160 cm⁻¹. -1 The characteristic absorption of Si-H is visible nearby; compared with curve (c), the cured curve (d) still retains the main characteristic absorption of silicone rubber and synthetic mica, and is approximately 2160 cm⁻¹. -1 The weakening of Si-H absorption is consistent with the results of hydrogen-containing silicone oil participating in the hydrosilylation curing reaction. This spectrum is used to confirm the presence of relevant functional groups and inorganic phases in the cured sample, but not to determine the spatial location of mica flakes within the microparticles.

[0052] (II) Preparation of sealing silicone gel materials: Formulation of sealing silicone gel material (by weight): 100 parts of vinyl-terminated polydimethylsiloxane (47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane); 7.0 parts of hydrogen-containing silicone oil; 8.0 parts of vinyl MQ silicone resin dispersion; 14.0 parts of sheet-like composite elastic microparticles (median particle size 165 μm); 3.0 parts of medium specific surface area hydrophobic fumed silica; 1.25 parts of adhesion promoter (0.76 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.49 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mass ratio 1:0.65); 0.30 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 3500 mg / kg); 0.035 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0053] S1. 3.0 parts of hydrophobic fumed silica were dried at 120℃ for 3 hours, and 14.0 parts of the layered composite elastic microparticle component were dried at 72℃ for 3 hours. At 28℃, 47.5 parts of first vinyl-terminated polydimethylsiloxane, 52.5 parts of second vinyl-terminated polydimethylsiloxane, 8.0 parts of vinyl MQ silicone resin dispersion, and the dried 3.0 parts of hydrophobic fumed silica were added to a stirring apparatus and stirred at 800 rpm for 20 minutes. The dried 14.0 parts of the layered composite elastic microparticle component and 1.25 parts of adhesion promoter were added, and the mixture was stirred at 28℃ and 600 rpm for 20 minutes. Subsequently, the mixture was degassed for 15 minutes under a vacuum of -0.090 MPa to obtain the basic mixture.

[0054] S2. Add 0.035 parts of 1-ethynylcyclohexanol and 7.0 parts of hydrogen-containing silicone oil to the basic mixture, and stir for 8 min at 25°C and 350 r / min. Then add 0.30 parts of platinum-vinylsiloxane complex catalyst working solution with a platinum content of 3500 mg / kg, and stir for 5 min at 25°C and 300 r / min to obtain a silica gel mixture.

[0055] S3. Degas the silicone gel mixture under a vacuum of -0.092 MPa for 10 min, then inject it into the area to be sealed at the joint connection of the humanoid robot (the connection gap between adjacent joint shells), with a filling layer thickness of 2.0 mm, and cure it at 70°C for 90 min.

[0056] Example 2 (I) Preparation of layered composite elastic microparticle components: Raw material formulation for the preparation of layered composite elastic microparticle components (by mass parts): 100 parts of vinyl-terminated polydimethylsiloxane (35.0 parts of first vinyl-terminated polydimethylsiloxane and 65.0 parts of second vinyl-terminated polydimethylsiloxane); 3.0 parts of hydrogen-containing silicone oil; 6.0 parts of low specific surface area hydrophobic fumed silica; 12.0 parts of synthetic mica (using synthetic fluorophlogopite powder, with a median particle size D50 of 5±1μm and a sheet thickness in the range of 0.2-1.5μm); 1.5 parts of vinyltriethoxysilane; 0.05 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 2000mg / kg); 0.01 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0057] A1. 12.0 parts of synthetic mica were dried in a forced-air drying oven at 105℃ for 2 hours. The dried synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:8 (ethanol:water mass ratio 90:10). 1.5 parts of vinyltriethoxysilane were added, and the pH of the system was adjusted to 4.2 using acetic acid. The mixture was stirred at 50℃ and 400 rpm for 60 minutes. After the reaction was complete, the mixture was filtered, washed twice with an ethanol-water mixture at a mass ratio of 90:10, and the filter cake was dried at 70℃ for 4 hours to obtain silane-treated synthetic mica.

[0058] A2. At 20°C, 35.0 parts of first vinyl-terminated polydimethylsiloxane and 65.0 parts of second vinyl-terminated polydimethylsiloxane, along with 6.0 parts of hydrophobic fumed silica, were added to a reactor and stirred at 600 rpm for 15 min. Then, 0.01 parts of 1-ethynylcyclohexanol and 3.0 parts of hydrogen-containing silicone oil were added, and the mixture was stirred at 300 rpm for 5 min. Finally, 0.05 parts of a platinum-vinylsiloxane complex catalyst working solution with a platinum content of 2000 mg / kg were added, and the mixture was stirred at 200 rpm for 2 min to obtain a silicone rubber reaction mixture.

[0059] A3. The silicone rubber reaction mixture was added to a 0.8% (w / w) polyvinyl alcohol aqueous solution, with a mass ratio of 1:4. The mixture was dispersed at 900 r / min for 8 min to form silicone rubber droplets. The rotation speed was adjusted to 400 r / min, and the silane obtained in A1 was added over 5 min to treat the synthesized mica. Stirring continued for 10 min. The temperature was then raised to 65℃ and maintained for 60 min to crosslink the silicone rubber droplets, resulting in crosslinked silicone rubber droplets.

[0060] A4. The cross-linked silicone rubber droplets were filtered, washed twice with deionized water, dried at 60℃ for 6 hours, graded using standard sieves, and the median volumetric particle size was determined to be 80 μm by laser diffraction, thus obtaining the sheet-like composite elastic microparticle component.

[0061] (II) Preparation of sealing silicone gel materials: Formulation of sealing silicone gel material (by weight): 100 parts of vinyl-terminated polydimethylsiloxane (35.0 parts of first vinyl-terminated polydimethylsiloxane and 65.0 parts of second vinyl-terminated polydimethylsiloxane); 4.0 parts of hydrogen-containing silicone oil; 4.0 parts of vinyl MQ silicone resin dispersion; 8.0 parts of sheet-like composite elastic microparticles (median particle size 80 μm); 1.0 part of low specific surface area hydrophobic fumed silica; 0.5 parts of adhesion promoter (0.385 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.115 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mass ratio 1:0.30); 0.10 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 2000 mg / kg); 0.01 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0062] S1. 1.0 part of hydrophobic fumed silica was dried at 110℃ for 2 hours, and 8.0 parts of the layered composite elastic microparticle component was dried at 65℃ for 2 hours. At 20℃, 35.0 parts of first vinyl-terminated polydimethylsiloxane, 65.0 parts of second vinyl-terminated polydimethylsiloxane, 4.0 parts of vinyl MQ silicone resin dispersion, and the dried 1.0 part of hydrophobic fumed silica were added to a stirring apparatus and stirred at 600 rpm for 15 minutes. Then, 8.0 parts of the dried layered composite elastic microparticle component and 0.5 parts of adhesion promoter were added, and the mixture was stirred at 20℃ and 400 rpm for 15 minutes. Subsequently, the mixture was degassed under a vacuum of -0.080 MPa for 10 minutes to obtain the basic mixture.

[0063] S2. Add 0.01 parts of 1-ethynylcyclohexanol and 4.0 parts of hydrogen-containing silicone oil to the basic mixture, and stir for 5 min at 20℃ and 200 r / min. Then add 0.10 parts of platinum-vinylsiloxane complex catalyst working solution with a platinum content of 2000 mg / kg, and stir for 3 min at 20℃ and 200 r / min to obtain a silica gel mixture.

[0064] S3. Degas the silicone gel mixture under a vacuum of -0.085 MPa for 5 min, then inject it into the area to be sealed at the joint connection of the humanoid robot (the annular gap between the joint drive component and the joint shell), with a filling layer thickness of 0.5 mm, and cure it at 60°C for 45 min.

[0065] Example 3 (I) Preparation of layered composite elastic microparticle components: Raw material formulation for the preparation of layered composite elastic microparticle components (by mass parts): 100 parts of vinyl-terminated polydimethylsiloxane (60.0 parts of first vinyl-terminated polydimethylsiloxane and 40.0 parts of second vinyl-terminated polydimethylsiloxane); 8.0 parts of hydrogen-containing silicone oil; 16.0 parts of high specific surface area hydrophobic fumed silica; 30.0 parts of synthetic mica (using synthetic fluorophlogopite powder, with a median particle size D50 of 20±2μm and a sheet thickness in the range of 0.2-1.5μm); 4.0 parts of vinyltriethoxysilane; 0.25 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 5000mg / kg); 0.06 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0066] A1. 30.0 parts of synthetic mica were dried in a forced-air drying oven at 120℃ for 4 hours. The dried synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:15 (ethanol:water mass ratio 96:4). 4.0 parts of vinyltriethoxysilane were added, and the pH of the system was adjusted to 4.8 using acetic acid. The mixture was stirred at 60℃ and 800 rpm for 120 minutes. After the reaction was complete, the mixture was filtered, washed three times with an ethanol-water mixture at a mass ratio of 96:4, and the filter cake was dried at 85℃ for 8 hours to obtain silane-treated synthetic mica.

[0067] A2. At 30°C, 60.0 parts of first vinyl-terminated polydimethylsiloxane and 40.0 parts of second vinyl-terminated polydimethylsiloxane, along with 16.0 parts of hydrophobic fumed silica, were added to a reactor and stirred at 1000 rpm for 30 min. Then, 0.06 parts of 1-ethynylcyclohexanol and 8.0 parts of hydrogen-containing silicone oil were added, and the mixture was stirred at 600 rpm for 10 min. Finally, 0.25 parts of a platinum-vinylsiloxane complex catalyst working solution with a platinum content of 5000 mg / kg were added, and the mixture was stirred at 400 rpm for 5 min to obtain a silicone rubber reaction mixture.

[0068] A3. The silicone rubber reaction mixture was added to a 1.5% (w / w) polyvinyl alcohol aqueous solution, with a mass ratio of 1:8. The mixture was dispersed at 1500 r / min for 15 min to form silicone rubber droplets. The rotation speed was adjusted to 700 r / min, and the silane obtained in A1 was added over 10 min to treat the synthesized mica. Stirring continued for 20 min. The temperature was then raised to 80℃ and maintained for 180 min to crosslink the silicone rubber droplets, resulting in crosslinked silicone rubber droplets.

[0069] A4. The cross-linked silicone rubber droplets were filtered, washed three times with deionized water, dried at 75°C for 10 hours, graded using a standard sieve, and the median volumetric particle size was determined to be 250 μm by laser diffraction, thus obtaining the sheet-like composite elastic microparticle component.

[0070] (II) Preparation of sealing silicone gel materials: Formulation of sealing silicone gel material (by weight): 100 parts of vinyl-terminated polydimethylsiloxane (60.0 parts of first vinyl-terminated polydimethylsiloxane and 40.0 parts of second vinyl-terminated polydimethylsiloxane); 10.0 parts of hydrogen-containing silicone oil; 12.0 parts of vinyl MQ silicone resin dispersion; 20.0 parts of sheet-like composite elastic microparticles (median particle size 250 μm); 5.0 parts of high specific surface area hydrophobic fumed silica; 2.0 parts of adhesion promoter (1.0 part of γ-glycidyl etheroxypropyltrimethoxysilane and 1.0 part of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mass ratio 1:1.00); 0.50 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 5000 mg / kg); 0.06 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0071] S1. 5.0 parts of hydrophobic fumed silica were dried at 130℃ for 4 hours, and 20.0 parts of the layered composite elastic microparticle component were dried at 80℃ for 4 hours. At 35℃, 60.0 parts of first vinyl-terminated polydimethylsiloxane, 40.0 parts of second vinyl-terminated polydimethylsiloxane, 12.0 parts of vinyl MQ silicone resin dispersion, and the dried 5.0 parts of hydrophobic fumed silica were added to a stirring apparatus and stirred at 1000 r / min for 30 min. The dried 20.0 parts of the layered composite elastic microparticle component and 2.0 parts of adhesion promoter were added, and the mixture was stirred at 35℃ and 800 r / min for 30 min. Subsequently, the mixture was degassed under a vacuum of -0.095 MPa for 20 min to obtain the basic mixture.

[0072] S2. Add 0.06 parts of 1-ethynylcyclohexanol and 10.0 parts of hydrogen-containing silicone oil to the basic mixture, and stir for 10 min at 30℃ and 500 r / min. Then add 0.50 parts of platinum-vinylsiloxane complex catalyst working solution with a platinum content of 5000 mg / kg, and stir for 6 min at 30℃ and 400 r / min to obtain a silica gel mixture.

[0073] S3. Degas the silicone gel mixture under a vacuum of -0.098 MPa for 15 min, then inject it into the area to be sealed at the joint connection of the humanoid robot (the circumferential gap where the joint cable leads out), with a filling layer thickness of 5.0 mm, and cure it at 80°C for 120 min.

[0074] Example 4 (I) Preparation of layered composite elastic microparticle components: Raw material formulation for the preparation of layered composite elastic microparticle components (by mass parts): 100 parts of vinyl-terminated polydimethylsiloxane (47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane); 5.5 parts of hydrogen-containing silicone oil; 11.0 parts of medium specific surface area hydrophobic fumed silica; 21.0 parts of synthetic mica (using synthetic fluorophlogopite powder, with a median particle size D50 of 12±2 μm and a sheet thickness in the range of 0.2-1.5 μm); 2.75 parts of vinyltriethoxysilane; 0.15 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 3500 mg / kg); 0.035 parts of alkynyl alcohol inhibitor (2-methyl-3-butyn-2-ol).

[0075] A1. 21.0 parts of synthetic mica were dried in a forced-air drying oven at 112℃ for 3 hours. The dried synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:11.5 (ethanol:water mass ratio 93:7). 2.75 parts of vinyltriethoxysilane were added, and the pH of the system was adjusted to 4.5 using acetic acid. The mixture was stirred at 55℃ and 600 rpm for 90 minutes. After the reaction was complete, the mixture was filtered, washed twice with an ethanol-water mixture at a mass ratio of 93:7, and the filter cake was dried at 78℃ for 6 hours to obtain silane-treated synthetic mica.

[0076] A2. At 25°C, 47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane, along with 11.0 parts of hydrophobic fumed silica, were added to a reactor and stirred at 800 rpm for 20 min. Then, 0.035 parts of 2-methyl-3-butyn-2-ol and 5.5 parts of hydrogen-containing silicone oil were added, and the mixture was stirred at 450 rpm for 8 min. Finally, 0.15 parts of a platinum-vinylsiloxane complex catalyst working solution with a platinum content of 3500 mg / kg were added, and the mixture was stirred at 300 rpm for 4 min to obtain a silicone rubber reaction mixture.

[0077] A3. The silicone rubber reaction mixture was added to a 1.15% (w / w) polyvinyl alcohol aqueous solution, with a mass ratio of 1:6. The mixture was dispersed at 1200 r / min for 12 min to form silicone rubber droplets. The rotation speed was adjusted to 550 r / min, and the silane obtained in A1 was added over 8 min to treat the synthesized mica. Stirring continued for 15 min. The temperature was then raised to 72℃ and maintained for 120 min to crosslink the silicone rubber droplets, yielding crosslinked silicone rubber droplets.

[0078] A4. The cross-linked silicone rubber droplets were filtered, washed three times with deionized water, dried at 68°C for 8 hours, graded using a standard sieve, and the median volumetric particle size was determined to be 165 μm by laser diffraction, thus obtaining the sheet-like composite elastic microparticle component.

[0079] (II) Preparation of sealing silicone gel materials: Formulation of sealing silicone gel material (by weight): 100 parts of vinyl-terminated polydimethylsiloxane (47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane); 7.0 parts of hydrogen-containing silicone oil; 8.0 parts of vinyl MQ silicone resin dispersion; 14.0 parts of layered composite elastic microparticle component (median particle size 165 μm); 3.0 parts of medium specific surface area hydrophobic fumed silica; 1.25 parts of adhesion promoter (0.76 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.49 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mass ratio 1:0.65); 0.30 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 3500 mg / kg); 0.035 parts of alkynyl alcohol inhibitor (2-methyl-3-butyn-2-ol).

[0080] S1. 3.0 parts of hydrophobic fumed silica were dried at 120℃ for 3 hours, and 14.0 parts of the layered composite elastic microparticle component were dried at 72℃ for 3 hours. At 28℃, 47.5 parts of first vinyl-terminated polydimethylsiloxane, 52.5 parts of second vinyl-terminated polydimethylsiloxane, 8.0 parts of vinyl MQ silicone resin dispersion, and the dried 3.0 parts of hydrophobic fumed silica were added to a stirring apparatus and stirred at 800 rpm for 20 minutes. The dried 14.0 parts of the layered composite elastic microparticle component and 1.25 parts of adhesion promoter were added, and the mixture was stirred at 28℃ and 600 rpm for 20 minutes. Subsequently, the mixture was degassed for 15 minutes under a vacuum of -0.090 MPa to obtain the basic mixture.

[0081] S2. Add 0.035 parts of 2-methyl-3-butyn-2-ol and 7.0 parts of hydrogen-containing silicone oil to the basic mixture, and stir for 8 min at 25°C and 350 r / min. Then add 0.30 parts of a platinum-vinylsiloxane complex catalyst working solution with a platinum content of 3500 mg / kg, and stir for 5 min at 25°C and 300 r / min to obtain a silica gel mixture.

[0082] S3. Degas the silicone gel mixture under a vacuum of -0.092 MPa for 10 min, then inject it into the area to be sealed at the joint connection of the humanoid robot (the connection gap between adjacent joint shells), with a filling layer thickness of 2.0 mm, and cure it at 70°C for 90 min.

[0083] Example 5 (I) Preparation of layered composite elastic microparticle components: The preparation of the sheet-like composite elastic microparticle component is exactly the same as that in Example 1(a).

[0084] (II) Preparation of sealing silicone gel materials: Formulation of sealing silicone gel material (by weight): 100 parts of vinyl-terminated polydimethylsiloxane (47.5 parts of first vinyl-terminated polydimethylsiloxane and 52.5 parts of second vinyl-terminated polydimethylsiloxane); 7.0 parts of hydrogen-containing silicone oil; 8.0 parts of vinyl MQ silicone resin dispersion; 14.0 parts of sheet-like composite elastic microparticles (median particle size 165 μm); 3.0 parts of medium specific surface area hydrophobic fumed silica; 1.25 parts of adhesion promoter (0.625 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.625 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mass ratio 1:1.00); 0.30 parts of platinum-vinylsiloxane complex catalyst working solution (platinum content 3500 mg / kg); 0.035 parts of alkynyl alcohol inhibitor (1-ethynylcyclohexanol).

[0085] S1. 3.0 parts of hydrophobic fumed silica were dried at 120℃ for 3 hours, and 14.0 parts of the layered composite elastic microparticle component were dried at 72℃ for 3 hours. At 28℃, 47.5 parts of first vinyl-terminated polydimethylsiloxane, 52.5 parts of second vinyl-terminated polydimethylsiloxane, 8.0 parts of vinyl MQ silicone resin dispersion, and the dried 3.0 parts of hydrophobic fumed silica were added to a stirring apparatus and stirred at 800 rpm for 20 minutes. The dried 14.0 parts of the layered composite elastic microparticle component and 1.25 parts of adhesion promoter (0.625 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.625 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane) were added, and the mixture was stirred at 28℃ and 600 rpm for 20 minutes. Subsequently, the mixture was degassed for 15 minutes under a vacuum of -0.090 MPa to obtain the basic mixture.

[0086] S2. Add 0.035 parts of 1-ethynylcyclohexanol and 7.0 parts of hydrogen-containing silicone oil to the basic mixture, and stir for 8 min at 25°C and 350 r / min. Then add 0.30 parts of platinum-vinylsiloxane complex catalyst working solution with a platinum content of 3500 mg / kg, and stir for 5 min at 25°C and 300 r / min to obtain a silica gel mixture.

[0087] S3. Degas the silicone gel mixture under a vacuum of -0.092 MPa for 10 min, then inject it into the area to be sealed at the joint connection of the humanoid robot (the connection gap between adjacent joint shells), with a filling layer thickness of 2.0 mm, and cure it at 70°C for 90 min.

[0088] Comparative Example 1 Comparative Example 1 did not add the sheet-like composite elastic microparticle component, but replaced 14.0 parts of the sheet-like composite elastic microparticle component with an equal amount of pure vinyl-terminated polydimethylsiloxane; the substitute was composed of first vinyl-terminated polydimethylsiloxane and second vinyl-terminated polydimethylsiloxane in a mass ratio of 47.5:52.5. The total amount of vinyl-terminated polydimethylsiloxane in the sealing silicone gel material formulation was 114.0 parts, of which 54.2 parts were first vinyl-terminated polydimethylsiloxane and 59.8 parts were second vinyl-terminated polydimethylsiloxane. It did not contain the sheet-like composite elastic microparticle component, and the remaining components and amounts were the same as in Example 1.

[0089] Comparative Example 2 Comparative Example 2 replaced the sheet-like composite elastic microparticle component with a direct mixture of untreated synthetic mica and silicone rubber particles. The mixture was prepared as follows: a silicone rubber reaction mixture was prepared according to step A2 of Example 1 (I), and dispersed in an aqueous polyvinyl alcohol solution to form droplets and crosslink according to step A3 of Example 1 (I), but without adding silane to treat the synthetic mica in step A3; after crosslinking, it was filtered, washed, dried, and sieved according to step A4 to obtain mica-free silicone rubber particles. The silicone rubber particles were then physically mixed with untreated synthetic fluorophlogopite powder, the synthetic mica having a D50 of 12±2 μm and a sheet thickness in the range of 0.2-1.5 μm; the two were mixed according to the feeding ratio described in Example 1 to obtain a direct mixture. In the formulation of the sealing silicone gel material, 14.0 parts of this direct mixture replaced the sheet-like composite elastic microparticle component, with the remaining components and amounts the same as in Example 1.

[0090] Comparative Example 3 Comparative Example 3 did not add synthetic mica to the layered composite elastic microparticle component. In the raw material formulation for preparing the layered composite elastic microparticle component, 21.0 parts of synthetic fluorophlogopite powder were removed; the remaining raw materials and amounts were the same as in Example 1. The synthetic mica treatment and addition steps were omitted from the preparation process, resulting in mica-free silicone rubber elastic microparticles. In the sealing silicone gel material formulation, 14.0 parts of the mica-free silicone rubber elastic microparticles were used to replace the layered composite elastic microparticle component; the remaining components and amounts were the same as in Example 1.

[0091] Comparative Example 4 Comparative Example 4 did not add an adhesion promoter. In the sealant silicone gel material formulation, 1.25 parts of the adhesion promoter were removed; the remaining components and amounts were the same as in Example 1. In the preparation process, after adding the layered composite elastic microparticle component in step S1, no adhesion promoter was added; the mixture was directly stirred and degassed; the remaining steps were the same as in Example 1. The formulation and preparation process of the layered composite elastic microparticle component were the same as in Example 1.

[0092] Comparative Example 5 Comparative Example 5 did not add vinyl MQ silicone resin dispersion. In the sealant silicone gel material formulation, 8.0 parts of vinyl MQ silicone resin dispersion were removed; the remaining components and amounts were the same as in Example 1. In the preparation process, vinyl MQ silicone resin dispersion was not added in step S1; the remaining steps were the same as in Example 1. The raw material formulation and preparation process for the layered composite elastic microparticle component were the same as in Example 1.

[0093] Comparative Example 6 Comparative Example 6 used untreated synthetic mica in the layered composite elastic microparticle component. In the preparation of the layered composite elastic microparticle component, 2.75 parts of vinyltriethoxysilane were removed from the raw material formulation; the synthetic fluorophlogopite powder was not subjected to A1 silane treatment, but was only dried at 112°C for 3 hours before use, with a D50 of 12±2 μm and a layer thickness in the range of 0.2-1.5 μm. The remaining raw materials and amounts were the same as in Example 1. The A1 silane treatment step was omitted in the preparation process, and untreated synthetic mica was added in step A3; the remaining parameters were the same as in Example 1. The formulation and preparation process of the sealing silicone gel material were the same as in Example 1.

[0094] Comparative Example 7 In Comparative Example 7, the amount of hydrophobic fumed silica with medium specific surface area was adjusted to 4.0 parts in the layered composite elastic microparticle component, and its BET specific surface area remained at 150-190 m². 2 / g. In the preparation of the layered composite elastic microparticle component, the amount of medium specific surface area hydrophobic fumed silica in the raw material formulation was changed from 11.0 parts to 4.0 parts, while the remaining raw materials and their amounts were the same as in Example 1. The preparation process, the formulation of the sealing silicone gel material, and the preparation process were the same as in Example 1.

[0095] Comparative Example 8 Comparative Example 8 used natural mica instead of synthetic mica. In the raw material formulation for the preparation of the layered composite elastic microparticle component, 21.0 parts of synthetic fluorophlogopite powder were replaced with 21.0 parts of micronized muscovite; the natural mica was graded before use to achieve a D50 of 12±2 μm and a layer thickness within the range of 0.2-1.5 μm. The remaining raw materials and amounts were the same as in Example 1. In the preparation process, step A1 involved silane treatment of the natural mica under the same conditions as for the synthetic mica; the remaining steps were the same as in Example 1. The formulation and preparation process of the sealing silicone gel material were the same as in Example 1.

[0096] Performance testing: The sealing silicone gel materials prepared in Examples 1-5 and Comparative Examples 1-8 were subjected to performance tests. The test samples were prepared as follows: the silicone gel mixtures prepared in each example and comparative example were vacuum degassed and then injected into molds of a specified shape. They were cured according to the curing conditions of their respective examples or comparative examples, and the test samples were obtained after demolding. For dustproof testing, the silicone gel mixture was injected into a test fixture simulating the joint connection of a humanoid robot. The fixture had a 2.0 mm wide and 15 mm deep gap between adjacent shells. After curing according to their respective curing conditions, the samples were tested. The IP5X or IP6X listed in Table 1 represents the judgment results of the simulated fixture under the test conditions of this application and is not equivalent to the overall protection level of the robot.

[0097] The structural observation method of the lamellar composite elastic microparticle component is as follows: the dried microparticles are directly fixed on the SEM sample stage to observe the surface morphology; the presence of gaps between visible lamellars and the formation of a continuous dense coating layer are used as the criteria for judging the surface morphology, and the three-dimensional distribution inside the microparticles is not determined based on this.

[0098] The test items and methods are as follows: 1. Shore A hardness: determined according to GB / T531.1, with a sample thickness of 6 mm and a test temperature of 23±2℃, and tested according to the number of samples and test points specified in the standard.

[0099] 2. Tensile strength and elongation at break: determined according to GB / T528, using type 2 dumbbell-shaped specimens, tensile speed 500 mm / min, and test temperature 23±2℃.

[0100] 3. Compression set: Determined according to GB / T7759, using type B specimens (diameter 13 mm, height 6.3 mm), compression rate 25%, test conditions 70℃×24h, and measured after recovery at 23±2℃ for 30 min.

[0101] 4. Water absorption rate: Cut the sample into square test pieces of 50mm×50mm×2mm, dry them at 70℃ for 24h and weigh them (m1). Soak them in deionized water at room temperature (23±2℃) for 168h, take them out and wipe the surface moisture with filter paper and weigh them (m2). Water absorption rate = (m2-m1) / m1×100%.

[0102] 5. Dustproof Judgment of Simulated Tooling: Dustproof testing was conducted according to the protection rating of enclosures (IP code) in GB / T4208. Talc powder was used as the test dust, with a dust concentration of 2 kg / m³. A vacuum was drawn to make the internal air pressure of the tooling 2 kPa lower than the external air pressure, and this was maintained for 8 hours. After the test, the dust intrusion inside the tooling was checked according to the judgment rules of GB / T4208. Table 1 lists the judgment results of this simulated tooling.

[0103] 6. Cyclic fatigue life: A dynamic mechanical fatigue testing machine was used to conduct cyclic compression-recovery tests on cylindrical samples with a diameter of 20 mm and a height of 10 mm at 50% compressive strain. The frequency was 1 Hz and the test temperature was 23 ± 2℃. At least 3 samples were tested for each material, and the number of cycles for each sample from the start of the cycle to the appearance of visible cracks or the load dropping to 80% of the initial value was recorded.

[0104] The performance test results are shown in the table below: Performance test data summary table: As shown in Table 1, under the product raw materials, feed amounts, curing conditions, and testing methods listed in this application, Examples 1-5 exhibited compression set of 11.8%-18.0%, water absorption of 0.14%-0.22%, and cyclic fatigue life of 8200-13200 cycles, achieving an IP6X rating in the simulated fixture. Comparative Examples 1-8 exhibited compression set of 16.0%-28.0%, water absorption of 0.21%-0.45%, and cyclic fatigue life of 3200-7200 cycles, achieving an IP5X rating in the simulated fixture. The above data only demonstrate the comparative relationship under the specific formulation and process conditions listed. Comparative Examples 1 and 5 simultaneously changed multiple feed factors and are only used for overall formulation comparison; the effects of mica surface treatment, lamellar surface distribution, adhesion promoters, and other components should be considered in conjunction with Comparative Examples 2-4, 6-8, and... Figure 1 , Figure 2 A comprehensive judgment.

[0105] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A silicone gel material for sealing joints of a humanoid robot, characterized in that, By weight, it comprises the following components: 100 parts vinyl-terminated polydimethylsiloxane, 4.0-10.0 parts hydrogen-containing silicone oil, 4.0-12.0 parts vinyl MQ silicone resin dispersion, 8.0-20.0 parts sheet-like composite elastic microparticles, 1.0-5.0 parts hydrophobic fumed silica, 0.5-2.0 parts adhesion promoter, 0.10-0.50 parts platinum-vinylsiloxane complex catalyst working solution, and 0.01-0.06 parts alkynyl alcohol inhibitor; The dispersion medium in the vinyl MQ silicone resin dispersion is vinyl-terminated polydimethylsiloxane; The 100 parts of the vinyl-terminated polydimethylsiloxane do not include the mass of the dispersion medium; The platinum content of the platinum-vinylsiloxane complex catalyst working solution is 2000-5000 mg / kg; The raw materials for preparing the layered composite elastic microparticle component, by weight, include: 100 parts vinyl-terminated polydimethylsiloxane, 3.0-8.0 parts hydrogen-containing silicone oil, 6.0-16.0 parts hydrophobic fumed silica, 12.0-30.0 parts synthetic mica, 1.5-4.0 parts vinyltriethoxysilane, 0.05-0.25 parts platinum-vinylsiloxane complex catalyst working solution, and 0.01-0.06 parts alkynyl alcohol inhibitor; The sheet-like composite elastic microparticle component includes silicone rubber elastic microparticles formed by crosslinking the vinyl-terminated polydimethylsiloxane and the hydrogen-containing silicone oil, and silane-treated synthetic mica sheets distributed at intervals on the surface of the silicone rubber elastic microparticles; the silane-treated synthetic mica sheets do not form a continuous dense coating layer.

2. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The vinyl-terminated polydimethylsiloxane is composed of a first vinyl-terminated polydimethylsiloxane and a second vinyl-terminated polydimethylsiloxane; The typical kinematic viscosity of the first vinyl-terminated polydimethylsiloxane at 25°C is 100 mmHg. 2 / s, with a vinyl mass fraction of 0.80%-1.20%; The typical kinematic viscosity of the second vinyl-terminated polydimethylsiloxane at 25°C is 5000 mm⁻¹. 2 / s, with a vinyl mass fraction of 0.10%-0.13%; The mass ratio of the first vinyl-terminated polydimethylsiloxane to the second vinyl-terminated polydimethylsiloxane is 35:65-60:

40.

3. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The kinematic viscosity of the hydrogen-containing silicone oil at 25°C is 25-35 mm. 2 / s, the molar fraction of methyl hydrogen siloxane structural units is 25%-35%.

4. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The vinyl MQ silicone resin dispersion contains 20%-25% vinyl MQ silicone resin by mass, and has a kinematic viscosity of 4500-7000 mmHg at 25°C. 2 / s, with a vinyl equivalent of 0.20-0.30 eq / kg.

5. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The median volumetric particle size of the lamellar composite elastic microparticle component is 80-250 μm; the median volumetric particle size of the synthetic mica is 5-20 μm, and the lamellar thickness is 0.2-1.5 μm; the BET specific surface area of ​​the hydrophobic fumed silica is selected from 90-130 m². 2 / g, 150-190m 2 / g or 225-275m 2 / g.

6. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The adhesion promoter is composed of γ-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, with a mass ratio of 1:0.30 to 1:1.00; the alkynol inhibitor is one or both of 1-ethynylcyclohexanol and 2-methyl-3-butyn-2-ol.

7. The sealing silicone gel material for the joint connections of a humanoid robot according to claim 1, characterized in that, The preparation method of the sheet-like composite elastic microparticle component includes the following steps: A1. The synthetic mica was dried at 105-120℃ for 2-4 hours. Then, the synthetic mica was dispersed in an ethanol-water mixture at a mass ratio of 1:8 to 1:15, wherein the mass ratio of ethanol to water in the ethanol-water mixture was 90:10 to 96:

4. Vinyltriethoxysilane was added, and the pH of the system was adjusted to 4.2-4.8 with acetic acid. The mixture was stirred at 50-60℃ and 400-800 r / min for 60-120 min, filtered, washed 2-3 times with an ethanol-water mixture, and dried at 70-85℃ for 4-8 hours to obtain silane-treated synthetic mica. A2. At 20-30℃, vinyl-terminated polydimethylsiloxane and hydrophobic fumed silica are stirred at 600-1000 r / min for 15-30 min, alkynyl alcohol inhibitors and hydrogen-containing silicone oil are added, and the mixture is stirred at 300-600 r / min for 5-10 min. Then, platinum-vinylsiloxane complex catalyst is added, and the mixture is stirred at 200-400 r / min for 2-5 min to obtain a silicone rubber reaction mixture. A3. The silicone rubber reaction mixture is added to a polyvinyl alcohol aqueous solution with a mass fraction of 0.8%-1.5%, wherein the degree of alcoholysis of the polyvinyl alcohol is 87.0%-89.0%; the mass ratio of the silicone rubber reaction mixture to the polyvinyl alcohol aqueous solution is 1:4-1:8, and dispersed at 900-1500 r / min for 8-15 min to form silicone rubber droplets; the rotation speed is adjusted to 400-700 r / min, and the silane-treated mica is added within 5-10 min, and stirring is continued for 10-20 min, followed by holding at 65-80℃ for 60-180 min to obtain crosslinked silicone rubber droplets; A4. Filter the cross-linked silicone rubber droplets, wash them 2-3 times with deionized water, dry them at 60-75℃ for 6-10 hours, and sieve them to obtain a layered composite elastic microparticle component with a median particle size of 80-250 μm.

8. A method for preparing a sealing silicone gel material for the joint connection of a humanoid robot according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Add vinyl-terminated polydimethylsiloxane, vinyl MQ silicone resin dispersion and hydrophobic fumed silica to a stirring device and stir for 15-30 min at 20-35℃ and 600-1000 r / min; add sheet composite elastic microparticle component and adhesion promoter, stir for 15-30 min at 20-35℃ and 400-800 r / min, and then degas for 10-20 min under a vacuum of -0.095 to -0.080 MPa to obtain the basic mixture; S2. Add alkynyl alcohol inhibitor and hydrogen-containing silicone oil to the basic mixture, and stir for 5-10 min at 20-30℃ and 200-500 r / min; then add platinum-vinylsiloxane complex catalyst, and stir for 3-6 min at 20-30℃ and 200-400 r / min to obtain a silicone gel mixture. S3. Degas the silicone gel mixture under a vacuum of -0.098 to -0.085 MPa for 5-15 minutes, then inject it into the area to be sealed at the joint connection of the humanoid robot, and cure it at 60-80°C for 45-120 minutes.

9. The method for preparing the sealing silicone gel material for the joint connection of a humanoid robot according to claim 8, characterized in that, In step S1, the hydrophobic fumed silica is dried at 110-130℃ for 2-4 hours before being added to the stirring equipment; the sheet-like composite elastic microparticle component is dried at 65-80℃ for 2-4 hours before being added to the stirring equipment; the material temperature in both steps S1 and S2 is controlled below 35℃.

10. The method for preparing the sealing silicone gel material for the joint connection of a humanoid robot according to claim 8, characterized in that, In step S3, the area to be sealed is the connection gap between adjacent joint housings, the annular gap between the joint drive assembly and the joint housing, or the circumferential gap at the joint cable lead-out position; the thickness of the filling layer formed by the silicone gel mixture before curing is 0.5-5.0 mm.